PENGARUH PENERAPAN MODEL PEMBELAJARAN ROTATING TRIO EXCHANGE (RTE) TERHADAP MOTIVASI BELAJAR PKN SISWA KELAS VII SMP NEGERI 25 PEKANBARU - Masitoh, Siti; Erlinda, Sri; Supentri, Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research is motivated by the low level of motivation of students in Pekanbaru 25 Middle School, experimental research entitled The Effect of Application of Rotating Trio Exchange (RTE) Learning Model on PKn Learning Motivation. PKn learning motivation of class VII students in Pekanbaru State Middle School 25. The formulation of the problem in this study is